2010
DOI: 10.1111/j.1471-1842.2010.00878.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and publication patterns of theses from a Peruvian medical school

Abstract: Background: Many medical schools require a student thesis before graduation. Publishing results in a peer-reviewed journal could be an indicator of scientific value and acceptability by the scientific community. The publication pattern of theses published by medical students in Peru is unknown. The aim of this study was to assess the characteristics and publication pattern of theses in biomedical-indexed journals conducted by medical students in a university with the highest research output in Peru. Methods: D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1
35

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 20 publications
4
40
1
35
Order By: Relevance
“…AIn an ot her study, 482 medi cal the ses we re re gis te red bet we en 2000 and 2003; 85 (17.6%) we re pub lis hed in bi o me di calin de xed jo ur nals in Pe ru. 3 A study in In di a showed that 30% of the ses-re la ted re se arch con duc ted in a uni ver sity me di cal col le ge was pub lis hed in inde xed journals. 1 In a study con duc ted in Fin land, the per cen ta ge of dip lo ma the ses pub lis hed is (23.8%).…”
Section: Figurementioning
confidence: 99%
“…AIn an ot her study, 482 medi cal the ses we re re gis te red bet we en 2000 and 2003; 85 (17.6%) we re pub lis hed in bi o me di calin de xed jo ur nals in Pe ru. 3 A study in In di a showed that 30% of the ses-re la ted re se arch con duc ted in a uni ver sity me di cal col le ge was pub lis hed in inde xed journals. 1 In a study con duc ted in Fin land, the per cen ta ge of dip lo ma the ses pub lis hed is (23.8%).…”
Section: Figurementioning
confidence: 99%
“…In similar studies around the world, the rates are as follows: 23.8% in Finland, 17% in France, 30% in India and 17.6% in Peru. [3,6,11,12] In our study, the publication rate of theses in international SCI and SCI-E journals was 36.3%, compared to 26.1% in other national or international journals. The total publication rate was 62.4%.…”
Section: Discussionmentioning
confidence: 90%
“…The publication rate is between 1.2% and 52.3%. [1][2][3][4][5][6] There are many reasons why the publication rates are so low, such as the work involved, time limitations, and fact that the students consider a thesis as only required to complete their specialization training. After some time, students no longer consider publishing their work, and there are no regulations to support or enforce the publication of theses.…”
mentioning
confidence: 99%
“…Diğer ülkelerle karşılaştırıldığında bu oranların oldukça düşük kaldığı saptanır. Peru'da Tıp fakülteleri-ni bitirme tezlerini inceleyen bir araştırmada 2000-2003 yılları arasında 482 tez kaydının bulunduğu ve bunların %17,6'sının yayın haline gelmiş olduğu, %5,8'sinin medline'da taranan dergilerde olduğu bildirilmektedir (6). Bu araştırma, uzmanlık değil tıp fakültesi bitirme tezlerinin incelenmesi açısından ülkemizden farklılık göstermekle birlikte medline'da listelenen dergilerde yayınlanma oranları birbirine yakındır.…”
Section: Tezlerin Makale Olarak Yayınlanmasıunclassified